PENGARUH FREKUENSI PEMUTARAN DAN POSISI TELUR PADA KEBERHASILAN PENETASAN TELUR AYAM KAMPUNG (Gallus gallus Domesticus) - Eoudia, Jecqueline C. M.; Lambey, Lucia J.; Saerang, Josephine L. P.; Nangoy, Fredy J. (Universitas Sam Ratulangi, 2019)
EFFECT OF TURNING FREQUENCY AND EGG POSITION ON HATCHABILITY OF CHICKEN EGGS (Gallus gallus Domesticus). This study aimed to determine effect of turning frequency and egg position on the hatching ability of chicken eggs. Study was conducted using 162 eggs of local hens inserted into hatching machine withcapacity of 300 eggs and implemented for 24 days. The experimental design of the completely factorial randomized design was applied consisting of 9 treatments and 3 replications. The two treatment factors were turning frequency consisted of 2 times a day, 3 times a day, 4 times a day, and egg position of 300, 600, and 900. The results of the analysis show that the effect of the turning frequency did not show a significant effect (P>0.05) on hatchability. However, egg position had a significant effect (P<0.5) on hatchability. There was no interaction between turning frequency and egg position againt hatchability and mortality. The conclusion of this research was the turning frequency of 2 times a day with egg slope position of 300 produced high hatchability and low level of mortality. Keywords : Egg turning frequency and position, hatchability, local hen.